2022
DOI: 10.3390/jcm11216274
|View full text |Cite
|
Sign up to set email alerts
|

Early Stages of Age-Related Macular Degeneration: Racial/Ethnic Differences and Proposal of a New Classification Incorporating Emerging Concept of Choroidal Pathology

Abstract: The progression of age-related macular degeneration (AMD) is determined by environmental and genetic factors, and phenotypic or molecular risk factors have been investigated extensively. Interestingly, risk factor profiles for advanced AMD differ among individuals, and one of the causes of variation may be explained by their ethnic background. Recent advances in retinal imaging technology have led to the identification of previously unrecognized risk factors for advanced AMD on optical coherence tomography (OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…A study has shown that CHO is related to the risk of developing early-stage AMD, but this was not confirmed in our study [ 39 ]. The main clinical feature of early AMD is the appearance of drusen, which is directly related to lipid metabolism [ 40 ]. Therefore, combined with our research results, the role of lipid metabolism in the development of early AMD is further confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that CHO is related to the risk of developing early-stage AMD, but this was not confirmed in our study [ 39 ]. The main clinical feature of early AMD is the appearance of drusen, which is directly related to lipid metabolism [ 40 ]. Therefore, combined with our research results, the role of lipid metabolism in the development of early AMD is further confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Dry AMD, also known as a non-exudative type of macular degeneration, is characterized by the presence of drusen, which are tiny yellow opaque deposits between RPE and BrM [ 49 ]. These extracellular deposits varying in size and density appear as the earliest features of macular degeneration [ 50 ]. AMD is mainly categorized into early, intermediate, and advanced forms.…”
Section: Reviewmentioning
confidence: 99%
“…The other spectrum of AMD encompasses the neovascular form or exudative/wet type of AMD, where new blood vessels proliferate into the sub-RPE or subretinal spaces [ 50 ]. The development of CNV causes leakage of abnormal vessels resulting in hemorrhage and even serious complications such as RPE detachment, leading to rapid sight loss [ 55 ].…”
Section: Reviewmentioning
confidence: 99%
“…The FFA can categorize n AMD into occult (type 1) MNV, classic (type 2) MNV, microscopic classic MNV, retinal angiomatous proliferation (RAP), and polypoid choroidal vasculopathy (PCV).Farecki et al [36] concluded that type 1 CNVs appeared larger, were poorly demarcated from the peripheral vasculature, and were seen primarily in the choroidal capillary layer, which is in the sub-RPE layer, whereas type 2 CNVs appeared smaller, were more well demarcated, and were predominantly found in the outer layers of the retina, with more extension into the subretinal space.RAP originates from the deep retinal capillary plexus, and its initial location is within the retina, growing toward the RPE.The incidence of RAP in n AMD primary cases is 10-15% [37,38] .PCV was initially recognized as a choroidal disease, and the 2020…”
Section: Hotspots and Emerging Frontiers On Ranibizumab And Amdmentioning
confidence: 99%